SINTESIS DAN KARAKTERISASI CROSSLINK KITOSAN DENGAN TRIPOLIFOSFAT pH 3 - Mardiyah Kurniasih; Nurul Hidayat Aprilita; Indriana Kartini (Universitas Jenderal Soedirman, 2011)
Chitosan is polycationic in acidic media and can interact with negatively charged species such as tripolyphosphate (TPP), which is a nontoxic crosslinking agent. The synthesis of TPP crosslinked chitosan was perfomed by reacting TPP solution (pH 3) with chitosan solution. The aim of this study was to prepared and characterize the crosslinked chitosan-tripolyphosphate samples. Characterization included determination of water and ash degree, moreover crosslinked chitosan-tripolyphosphate powder characterize with FTIR and XRD spectroscopy. The result showed that process efficiency of crosslinked chitosan-tripolyphosphate was 88.49%, with degree of water and ash were 25.70 and 16.72%, respectively.